2011
DOI: 10.1080/10807039.2011.571078
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Area-Based Yield Crop Risk Insurance in China

Abstract: Area-based yield insurance (AYI) is a kind of index insurance that can eliminate asymmetric information problems (adverse selection and moral hazard) and reduce transaction cost. It is important in managing crop risk for developing countries such as China, which has many small farms. However, the biggest challenge in index insurance is basis risk. In this regard, can AYI be used in China? Is AYI competitive with traditional multi-peril crop insurance (MPCI)? What are the principal factors affecting the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A number of areas in China sometimes face severe weather and agricultural disasters (Zhang et al, 2011;Boyd et al, 2011). One such area is Western China, where the possibility exists for severe cyclical droughts.…”
Section: Background Regarding Agricultural Risk In Inner Mongolia and Chinamentioning
confidence: 99%
“…A number of areas in China sometimes face severe weather and agricultural disasters (Zhang et al, 2011;Boyd et al, 2011). One such area is Western China, where the possibility exists for severe cyclical droughts.…”
Section: Background Regarding Agricultural Risk In Inner Mongolia and Chinamentioning
confidence: 99%
“…The weather station could have favorable weather, while the farmer some distance away from the weather station could face adverse weather and crop losses, and not receive an indemnity payment. This is known as "basis risk," and is a main challenge regarding weather index insurance (Woodard and Garcia, 2008;Fuchs and Wolff, 2011;Norton et al, 2013;Zhang et al, 2011;Paulson et al, 2010;Elabed et al, 2013;Clarke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. () empirically modeled area‐based insurance and MPCI for wheat farmers in two counties in China. The authors concluded that while area‐based insurance can reduce asymmetric information issues relative to MPCI, it introduces basis risk for farmers.…”
Section: Introductionmentioning
confidence: 99%